Enhancing Junior High School Literacy: Incorporating Luwu Cultural Heritage into Reading Materials - Tompo, Dewi Sri; Sahraini, Sahraini; Thayyib, Magfirah (VELES Voices of English Language Education Society, 2023)
Integrating local culture into language material leads to improving the students’ reading skills. Conducted in South Sulawesi's Luwu Regency, the research employs the ADDIE model for development and assessment. Participants included five English teachers and 25 eighth-grade students from (Junior High School) SMP Negeri 4 Belopa. During the analysis phase, teacher interviews and student questionnaires revealed a strong demand for culturally relevant materials, with 92% of students and 100% of teachers expressing a need for Luwu-based content. Subsequently, the design phase involved selecting texts reflective of local culture, guided by the needs analysis. The development phase produced an initial draft of a reading book comprising four chapters: "Heroes of Luwu," "Folklores of Luwu," "Enchantment of Luwu Tourism Objects," and "Traditional Foods of Luwu." Expert evaluations rated the content and language quality as 'good' with an average score of 83.75. Based on expert feedback, the draft underwent revisions. In the implementation phase, the revised reading materials were introduced in English classes at SMP Negeri 4 Belopa. Teachers rated the materials' effectiveness with an average score of 3.64 (agree), while student feedback was highly positive at 3.96 (strongly agree) on a 4-point scale, indicating the materials' practicality in an educational setting. The final evaluation phase involved refining the book based on teacher and student feedback, culminating in the dissemination of the final draft to several junior high schools within Luwu Regency. This study underscores the positive impact of culturally tailored educational materials on student engagement and skill development in language learning.